The Potential Therapeutic Effect of RNA Interference and Natural Products on COVID-19: A Review of the Coronaviruses Infection - Kalhori, Mohammad Reza; Saadatpour, Fatemeh; Arefian, Ehsan; Soleimani, Masoud; Farzaei, Mohammad Hosien; Aneva, Ina Yosifova; Echeverría, Javier (Frontiers in Pharmacology, 2021)
The SARS-CoV-2 virus was reported for the first time in Wuhan, Hubei Province, China, and causes respiratory infection. This pandemic pneumonia killed about 1,437,835 people out of 61,308,161cases up to November 27, 2020. The disease's main clinical complications include fever, recurrent coughing, shortness of breath, acute respiratory syndrome, and failure of vital organs that could lead to death. It has been shown that natural compounds with antioxidant, anticancer, and antiviral activities and RNA interference agents could play an essential role in preventing or treating coronavirus infection by inhibiting the expression of crucial virus genes. This study aims to introduce a summary of coronavirus's genetic and morphological structure and determine the role of miRNAs, siRNAs, chemical drugs, and natural compounds in stimulating the immune system or inhibiting the virus's structural and non-structural genes that are essential for replication and infection of SARS-CoV-2.